2016
DOI: 10.3201/eid2204.142050
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Genomic and Other Epidemiologic Data to Investigate and Control a Cross-Institutional Outbreak ofStreptococcus pyogenes

Abstract: Single-strain outbreaks of Streptococcus pyogenes infections are common and often go undetected. In 2013, two clusters of invasive group A Streptococcus (iGAS) infection were identified in independent but closely located care homes in Oxfordshire, United Kingdom. Investigation included visits to each home, chart review, staff survey, microbiologic sampling, and genome sequencing. S. pyogenes emm type 1.0, the most common circulating type nationally, was identified from all cases yielding GAS isolates. A tailor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 37 publications
(29 reference statements)
1
6
0
Order By: Relevance
“…For example, an emm1 outbreak lasting approximately 20 days that affected nine people (two invasive cases and seven non-invasive cases) associated with a maternity unit in the UK displayed zero SNP differences between all but one isolate [53]. Our data on within emm-type genomic diversity within NSW are similar to those from international studies, which have noted minimal divergence in clones over years [48,50,53,[57][58][59][60][61][62][63]. The genetic similarity indicates that many epidemiologically unrelated clones circulating within the community would be indistinguishable over short time frames thereby posing a false notion of an outbreak at a molecular level.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…For example, an emm1 outbreak lasting approximately 20 days that affected nine people (two invasive cases and seven non-invasive cases) associated with a maternity unit in the UK displayed zero SNP differences between all but one isolate [53]. Our data on within emm-type genomic diversity within NSW are similar to those from international studies, which have noted minimal divergence in clones over years [48,50,53,[57][58][59][60][61][62][63]. The genetic similarity indicates that many epidemiologically unrelated clones circulating within the community would be indistinguishable over short time frames thereby posing a false notion of an outbreak at a molecular level.…”
Section: Discussionsupporting
confidence: 77%
“…Whole-genome sequencing incorporated into surveillance programmes could assist our public-health teams in outbreak investigation, specifically to exclude outbreaks. Whole-genome sequencing has advantages over emm-typing and MLST for outbreak investigations for GAS because small genetic differences can be used to 'rule out' links in appropriate epidemiological contexts [48,50,62]. Key findings from an Australian healthcare and economic modelling study revealed that non-invasive (and locally invasive infection) accounted for approximately 90 % of healthcare presentations for S. pyogenes infections and 80 % of healthcare-associated costs [13].…”
Section: Discussionmentioning
confidence: 99%
“…The potential of WGS data analysis is huge as already demonstrated also for GAS where temporal and geographic relatedness between GAS isolates could be deduced ( 16 ). These new “omics” approaches may also provide rapid assessment of outbreaks by discriminating between closely related isolates, and produce extensive data on the virulome, including the associated regulatory mechanisms, and the antibiotic resistome ( 81 , 82 ). Hopefully, this review can be a reference for all those who work in the field of molecular epidemiology of GAS and may represent a milestone also to those who are approaching the problem using the recent next generation sequencing methodologies.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional bacterial typing methods may fail to confirm or refute an outbreak, because of insufficient discrimination between strains of the same lineage. WGS has been used successfully to investigate a small number of putative outbreaks, confirming a single causative strain that was distinct from the circulating population, which were otherwise indistinguishable by standard molecular typing methods 12 14 . Where epidemiological evidence for transmission is unclear or lacking, WGS data could potentially provide valuable supporting evidence to assist outbreak investigations 15 .…”
Section: Introductionmentioning
confidence: 98%
“…GAS is also associated with outbreaks of disease. Prior to WGS, probable outbreaks were defined when two or more cases of GAS infection, related by person or place, occurred within a year and isolates shared the same subtypes based on molecular typing 11 , 12 . Conventional bacterial typing methods may fail to confirm or refute an outbreak, because of insufficient discrimination between strains of the same lineage.…”
Section: Introductionmentioning
confidence: 99%